2021
DOI: 10.2478/ahr-2021-0011
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Imaging and Sensing Technologies for Field Phenotyping

Abstract: Over the past few decades, food production has been sufficient. However, climate change has already affected crop yields around the world. With climate change and population growth, threats to future food production come. Among the solutions to this crisis, breeding is deemed one of the most effective ways. However, traditional phenotyping in breeding is time-consuming as it requires thousands and thousands of individuals. Mechanisms and structures of stress tolerance have a great variability. Today, bigger em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 134 publications
0
1
0
Order By: Relevance
“…The introduction of newer, higher resolution thermal imaging systems that are compatible with UAVs have boosted the practical use of thermography in agriculture [38][39][40][41]. UAV thermal remote sensing applications include monitoring plant water stress, detection of diseases, and plant phenotyping [42][43][44]. It was reported that UAV thermal sensing could also offer remote sensing data for orchard management including water management by observing the fruit-tree canopy temperature variations [45][46][47].…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of newer, higher resolution thermal imaging systems that are compatible with UAVs have boosted the practical use of thermography in agriculture [38][39][40][41]. UAV thermal remote sensing applications include monitoring plant water stress, detection of diseases, and plant phenotyping [42][43][44]. It was reported that UAV thermal sensing could also offer remote sensing data for orchard management including water management by observing the fruit-tree canopy temperature variations [45][46][47].…”
Section: Introductionmentioning
confidence: 99%